Intensification of New Media Against the Spread of Fake News in the Post Truth Era - Anggrayni, Dewi; Siregar, Nur Choiro; Khairani, Shabrina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Digital developments through new media trace progress in the transformation of knowledge in digital format. The transformation of media into public consumption is a catalyst for many changes in the digital world, besides that, social media innovation has also become fertile ground for the spread of fake news throughout the world, thereby catalyzing the formation of the post truth era. The aim of the research is to determine the impact of the intensification of social media on the spread of fake news in the post truth era. This research uses a qualitative method with a literature review approach where the data source is adopted from several data that have been verified and have continuity with the research object. Based on the analysis results, there are 35 articles with related objects, the data is transferred to the Ms file. Excel and the main aspects lie in authorship patterns, contribution distribution by country, author ranking, affiliate contributions and country distribution. The results of the analysis of 35 articles from 2017 to 2020 revealed that there were 44 authors using journals with related topics. The most widely used research method in this topic is quantitative. The keywords used by the author are